PENGARUH PROGRAM CSR MELALUI INSTAGRAM TERHADAP BRAND IMAGE FOODCYCLE INDONESIA - Salsabila, Rifanda Hasna; Dwiantari, Ririh (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
On the Sehat Negeriku website from the Ministry of Health, nutrition and a balanced diet are things that determine the level of health and intelligence of society in Indonesia. Quoted from the United Nations Environment Program (UNEP), food waste in Indonesia is in first place in Southeast Asia. Then, this has encouraged the formation of groups that understand food waste, one of which is FoodCycle Indonesia which is a member of GFN or The Global Foodbanking Network from Indonesia. FoodCycle Indonesia carries out CSR activities to minimize food waste in Indonesia, one of which is through the FoodCycle Point program which is a place to distribute donations of food that is still fit for consumption, which has also been uploaded to FoodCycle Indonesia's Instagram to spread awareness. This research aims to determine the influence of the CSR program via Instagram on the brand image of Foodcycle Indonesia. This research uses a quantitative approach, to calculate sampling data using a survey with the Lemeshow formula because the population is unknown, can increase or decrease at any time and to distribute questionnaires to one hundred respondents of Foodcycle Indonesia Instagram followers. The data obtained was processed using the SPSS application using a simple linear test. The result is that there is a strong influence on the CSR program via Instagram on the FoodCycle Indonesia brand image. Respondents saw the dimensions of Community Volunteering and Strength of Brand Associations very well.